Radiofrequency ablation for treatment of thyroid follicular neoplasm with low SUV in PET/CT study. (1st January 2021) - Lin, Wei-Che; Tung, Yu-Cheng; Chang, Yen-Hsiang; Luo, Sheng-Dean; Chiang, Pi-Ling; Huang, Shun Chen; Chen, Wei-Chih; Chou, Chen-Kai; Su, Yan-Ye; Chen, Wen-Chieh; Chi, Shun-Yu; Baek, Jung Hwan
Abstract: Objectives: To evaluate the feasibility of radiofrequency ablation (RFA) on follicular neoplasm with low standard uptake value (SUV) in a Positron emission tomography (PET/CT) study. Methods: From January 2018 to July 2019, 86 consecutive patients were diagnosed with follicular neoplasm. Of the patients, 28 with PET/CT scans were enrolled in this study. All patients received ultrasound, fine/core needle aspiration, and PET/CT scan prior to treatment. In accordance with previous studies, we recommended 6 patients who had follicular neoplasm with SUVmax ≥5 undergo surgical resection due to an elevated suspicion of malignancy. For 22 patients SUVmax <5, RFA was performed using the moving shot technique. Ultrasound was performed 6 to 12 months after each procedure. Results: Statistically significant volume reductions during follow-up between values prior to RFA and 12 months post RFA were demonstrated (12.6 ± 20.9 vs. 2.4 ± 3.0 cm 3, p  < 0.001). Volume reduction ratios at 6–12 months (mean: 10.1 months) after RFA were 73.3% ± 17.7%. One patient presented with vocal cord palsy and recovered within 3 months after RFA. No postprocedural hypothyroidism occurred in the RFA patients. Conclusions: By using PET/CT, we can select patients with low SUV follicular neoplasm. RFA offers a safe and feasible alternative treatment option for patients unsuitable or unwilling to undergo surgery. KEY POINTS: By using positron emission tomography-computed tomography, we can distinguish low SUV follicular neoplasm for radiofrequency ablation. For low SUV follicular neoplasm, RF ablation offers a safe and effective alternative treatment option for patients unsuitable or unwilling to undergo surgery.